Improving argumentation through student blogs. (June 2016) - Kathpalia, Sujata S.; See, Eng Kiat
Abstract: Argumentation is essential for university students and many studies have been conducted to identify the best approaches to integrate argumentation into the university curriculum. However, there is still scope for improvement, especially in the area of online learning. This study assesses the use of argumentation in student blogs that were written before and after explicit instruction/activities on argumentation in a critical writing course. A total of 100 student blogs were analyzed and compared using a scoring framework for argumentation structure. It took into consideration presence of claims, evidence and counter-arguments as well as quality of argumentation. The findings showed that more than half the students were able to improve the structure and quality of argumentation in the post instruction blogs but more support is needed for the remaining students. Pedagogical strategies such as argumentation prompts and a peer-evaluation scheme are proposed to enhance argumentation in student blogs.